Tourism Intention of People Susceptible to Covid-19 in The New Normal - Ikasari Kusuma Wardhani; Hendrie Adji Kusworo; Dyah Widiyastuti (Universitas Gadjah Mada, 2022)
COVID-19 pandemic has triggered a fundamental challenge to tourism, that is mobility. While research on tourism intention have been growing since the beginning of the pandemic, there was a lack of attention on discussion about people who face less opportunity for tourism due to their vulnerable physical conditions or people at-risk to COVID-19. Therefore, this research purported to reveal the influence of tourism constraints on tourism intention of people categorized as physically vulnerable to COVID-19 in the new normal era. Data collection was conducted through an online survey to citizens of Jakarta belonging to middle age and elderly group from end of June to September 2021. Multiple regression analysis with SPSS is used to test the relationship between tourism constraints and tourism intention, and analyze data of 337 respondents. The study showed that tourism intention of people at-risk from COVID-19 can be classified as high with intrapersonal constraints being the only significant constraints. This implies that the significant effect of intrapersonal constraints is not powerful enough to reduce the tourism intention of people susceptible to COVID-19.